Brief Report: Dipyridamole Decreases Gut Mucosal Regulatory T-Cell Frequencies Among People With HIV on Antiretroviral Therapy. (15th December 2020) - Mallarino-Haeger, Christina; Abebe, Kaleab Z.; Jackson, Edwin K.; Zyhowski, Ashley; Klamar-Blain, Cynthia; Cyktor, Joshua C; Comer, Diane; Brand, Rhonda M.; Gillespie, Delbert G.; Holleran, Kyle; Mellors, John W.; McGowan, Ian; et al.
Abstract : Background: We had previously conducted a double-blind, randomized placebo-controlled, partial cross-over trial showing that 12 weeks of dipyridamole decreased CD8 + T-cell activation among treated HIV(+) individuals by increasing extracellular adenosine levels. Methods: In this substudy, rectosigmoid biopsies were obtained from 18 participants (9 per arm), to determine whether 12 weeks of dipyridamole affects mucosal immune cells. Participants randomized to placebo were then switched to dipyridamole for 12 weeks while the treatment arm continued dipyridamole for another 12 weeks. We evaluated T-cell frequencies and plasma markers of microbial translocation and intestinal epithelial integrity. Linear regression models on log-transformed outcomes were used for the primary 12-week analysis. Results: Participants receiving dipyridamole had a median 70.2% decrease from baseline in regulatory T cells ( P = 0.007) and an 11.3% increase in CD8 + T cells ( P = 0.05). There was a nonsignificant 10.80% decrease in plasma intestinal fatty acid binding protein levels in the dipyridamole arm compared with a 9.51% increase in the placebo arm. There were no significant differences in plasma levels of β-D-glucan. In pooled analyses, there continued to be a significant decrease in regulatory T cells (−44%; P = 0.004). There was also a trend for decreased CD4 + and CD8 + T-cell activation. Conclusion: Increasing extracellular adenosine levels using dipyridamole in virally suppressed HIV (+) individuals on antiretroviral therapy can affect regulation of gut mucosal immunity. Abstract : Supplemental Digital Content is Available in the Text.